2011
DOI: 10.1007/s00122-011-1528-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of seed lipoxygenase null traits in soybean line OX948

Abstract: The poor stability and off-flavors of soybean oil and protein products can be reduced by eliminating lipoxygenases from soybean seed. Mature seeds of OX948, a lipoxygenase triple null mutant line, do not contain lipoxygenase proteins. The objective of this study was to determine the molecular basis of the seed lipoxygenase null traits in OX948. Comparisons of the sequences for lipoxygenase 1 (Lx1) and lipoxygenase 2 (Lx2) genes in the mutant (OX948) with those in a line with normal lipoxygenase levels (RG10) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…The linoleate 9S-lipoxygenase 5-like sequence from soybean (gene ID: 100802887) has an intron 1 size of 1,956 bp, which is comparable with that of AhLOX7 . Based on soybean lipoxygenase gene information [ 38 , 39 ], the corresponding locations of AhLOX7 conserved histidine residues and fatty acid, iron, and oxygen binding sites were located in exons 7 to 9 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The linoleate 9S-lipoxygenase 5-like sequence from soybean (gene ID: 100802887) has an intron 1 size of 1,956 bp, which is comparable with that of AhLOX7 . Based on soybean lipoxygenase gene information [ 38 , 39 ], the corresponding locations of AhLOX7 conserved histidine residues and fatty acid, iron, and oxygen binding sites were located in exons 7 to 9 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on soybean lipoxygenase gene information [ 38 , 39 ], the corresponding locations of AhLOX7 conserved histidine residues and fatty acid, iron, and oxygen binding sites were located in exons 7 to 9 (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the VIR collection, there are samples with lx recessive alleles; adding them to the genome of commercial soybean genotypes will reduce lipoxygenase activity to get products that are less prone to undesirable oxidation. To date, these genes have been sequenced, and molecular markers can be used to speed up the search for the desired genotypes [50].…”
mentioning
confidence: 99%
“…Transcript levels of KTI3, CPI2, and NES1 increased to the maximum levels in ED059, indicating that PI and monoterpene may both contribute to conferring defense against insects. The biosynthesis of JA is essential for the production of induced defense responses to herbivores in many plants [37], and AOC3 is an important enzyme that promotes JA biosynthesis [38][39][40][41]. We found that H. armigera induced higher levels of JA and JA biosynthesis enzyme AOC3 gene expression in ED059 than in Tianlong 2.…”
Section: Discussionmentioning
confidence: 78%